The Implementation of Diary Writing to Enhance the Students’ Recount Text - Muhyiddin Aziz; Moh. Farid Maftuh; Halim Ahmad Faizin; Eda Maaliah; Muhammad Isa; Dian Palupi; Jannatul Laily Noviabahari; Alief Sutantohadi; Yulius Harry Widodo (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This classroom action research (CAR) aims to improve the level of students' English proficiency, specifically emphasizing their writing abilities.  The researchers aimed to investigate whether diary writing could elevate the writing abilities of second-semester students enrolled in the English Study Program at State Polytechnic of Madiun during the academic year 2024/2025. This research was carried out at Madiun State Polytechnic during the 2024/2025 academic year within Class A.  The researchers collected both qualitative and quantitative data.  The qualitative data collected from the scores obtained before the research and during its course, while quantitative data is utilized to compare the outcomes before and after the research, based on observations and interviews. The results of this study indicate that diary writing centered on visiting tourist attractions, memorable experiences, and national catastrophes can improve the writing proficiency of students enrolled in the English study program.  The impact of the increase is observable in the average scores of the pre-test and post-tests for each cycle, with values gradually ascending across cycles: pre-test 61, post-test cycle I 64, post-test cycle II 67, and post-test cycle III 71.